Daya Tahan Komunikasi Tradisional Komunitas Adat Bayan di Era Media Digital - Hartin Nur Khusnia; Dian Lestari Miharja; Diyah Indiyati; Muhlis Muhlis; Siti Chotijah (JCommsci - Journal Of Media and Communication Science, 2022)
In the current era of digital information and communication media, the Bayan indigenous people still firmly maintain the existence of traditional communication. The Bayan indigenous people are part of the Sasak people who live on the island of Lombok, West Nusa Tenggara. Traditional communication has an essential role in the social life of the community. Besides being able to bind relations between communities to be harmonious, it is also the identity of a society. In this regard, knowing how the Bayan indigenous community can maintain traditional communication in the digital media era is crucial. Data were collected by interview, observation, and documentation methods, with the resource persons being the village heads of Sukadana, Baturakit, and Bayan, as well as traditional leaders from the villages of Baturakit and Karang Bajo. The results show that the Bayan indigenous people continue to use digital media or the internet to add insight. However, the Bayan indigenous people also consistently maintain traditional communication. The still-functioning traditional institutions indicate this; still ongoing traditional rituals, including traditional rituals related to Islamic holidays, gawe urip rituals, namely rituals related to life, gawe pati rituals, namely traditional ceremonies related to death; and the functioning of customary awik-awik or customary law. The existence of the traditional communication of the Bayan indigenous people is the responsibility of the customs authorities, the Bayan indigenous people in general, and government policymakers. The factors that affect the durability of this traditional communication are: people's belief in the values ​​of their ancestors that are still firmly held, strong characterizations of traditional stakeholders as opinion leaders, and customary sanctions are also reasons for indigenous peoples to maintain traditional values ​​which are manifested in traditional communication.